Reinterpreting Islamic Legal Principles on Digital Identity and Biometric Authentication in the Era of Digital Transformation - Muhammad Yani; Mahfud Heru Fatoni (Indonesian Journal of Sharia and Islamic Sciences, 2026)
Digital identity and biometric authentication have become fundamental components of contemporary digital governance, creating new legal and ethical challenges for Islamic jurisprudence as conventional methods of identity verification are increasingly replaced by technologically mediated authentication systems. This study aims to reinterpret Islamic legal principles governing digital identity and biometric authentication through the integrated perspectives of uṣūl al-fiqh and maqāṣid al-sharī‘ah. A qualitative normative legal approach was employed using library research based on contemporary scholarly literature concerning Islamic law, digital governance, biometric technology, artificial intelligence, cybersecurity, privacy, and electronic authentication. The analysis demonstrates that the legitimacy of digital identity should be evaluated according to its ability to preserve justice, legal certainty, accountability, human dignity, and public welfare rather than the technological characteristics of authentication mechanisms alone. Biometric authentication is considered compatible with Islamic legal principles when supported by meaningful consent, proportional data governance, institutional responsibility, and effective privacy protection. The study proposes an integrated Islamic legal framework connecting digital identity, biometric authentication, ethical governance, and legal accountability, illustrating that Islamic jurisprudence possesses sufficient interpretive flexibility to respond constructively to digital transformation while maintaining its normative integrity. The proposed framework offers a conceptual foundation for future legal development and empirical research on digital governance within contemporary Muslim societies.